Dampka Variabel Makroekonomi Dan Iindeks Saham Global Terhadap Iindeks Harga LQ45 Di Bursa Efek Indonesia - Nuryasman MN; Verencia Permatasari (Jurnal Ekonomi, 2016)
The objective of this research was to examine the macroeconomics variable and global stock price index that influence LQ45 stock price. There were three fundamental macroeconomics variables in this study such as the Exchange rate of Rupiah, Interest Rate (SBI), and gold prices which were used with the global stock price index (Dow Jones Industrial Average) to examine their influence on LQ45 stock price. The sampling data used are 69 months from 2009 January until 2014 September. The selection of the sample used a non-probability sampling method, using the purposive sampling technique. The method used multiple regression analysis and Error Correction Model (ECM)using the software Eviews 6.0with a significance level of 5%. The result of the t-test shows that gold prices have not influenced LQ45 stock price. While the Exchange rate of the Rupiah, Interest Rate (SBI), and Dow Jones Industrial Average have influenced LQ45 stock price. The result of the F- test (jointly test) show that there are significant jointly between the Exchange rate of Rupiah, Interest Rate (SBI), gold price, and Dow Jones Industrial Average on LQ45 stock price. The result of ECM Models shows that between the Exchange rate of Rupiah, Interest Rate (SBI), gold price, and Dow Jones Industrial Average on LQ45 stock price, there was not able to achieve a balance in the long run.